Effectiveness of Nurse Led Interventions On Symptom Management Among Breast Cancer Patients In Selected Oncology Units, Bangalore - Rajanna, Sunitha; Shaji JC, Helen; Arunachalam, Lakshmi; Subbamma, Rama (Journal of Neonatal Surgery, 2025)
Background: Improving the quality of life of cancer survivor through the management of symptoms is a vital aspect of health care delivery system in the present scenario which often under investigated domain of the patients. Objective: This study examined the effectiveness of nurse-led teaching in the management of symptoms among breast cancer survivors in the selected oncology units at Shri Shankara cancer hospital. The present study aimed to enhance the breast cancer patients well-being through symptom management strategies based on Ernestine Wiedenbach‟s “The Helping Art of Clinical Nursing Theory”. Methods: A pre-test – post-test design was adopted and EORTOC QLQ 30 has been used to collect the required data. Results: Findings evidenced a highly significant improvement in the symptom management among breast cancer clients in the study group than the control group at p<0.001 Conclusion: Findings showed that nurse led interventions were effective in management of breast cancer symptoms along with medical interventions.